A comparative study on green building assessment (GBA) tool in Malaysia / Muhamad Isma Fahmi Mohd Ismail and Raja Rafidah Raja Muhammad Rooshdi - Mohd Ismail, Muhamad Isma Fahmi; Raja Muhammad Rooshdi, Raja Rafidah (2018)
Green Building or also known as sustainable building has become a trend nowadays due to massive construction happening that causes an impact towards the natural, built, social and economic environments. Malaysia also has developed its own green building assessment or rating tools to comprehend these green policies such as Green Building Index (GBI), Ph JKR, GREEN PASS and the latest one which is MyCREST. However, the differences in nature and assessment characteristics have caused complications for stakeholders in comparing the green building performance of each building by utilizing different assessment tools. Therefore, the main objectives of this study are to identify what are the green assessments available in Malaysia as well to determine what is the most important criteria for each of the tools, thus highlighting the main criteria taken into account when assessing a building. Each criterion from each tool will be compared and ranked according to their level of importance based on the survey obtained by the construction professional. The result shows that energy efficiency is the most important criterion with 94% agreement from the respondents in every assessment tools in Malaysia, followed by water efficiency, indoor environment quality respectively and sustainable site and management with 89% of each criterion.